The performance of Jatropha curcas Linn. Capsule Husk as feedstocks biogas in one phase anaerobic digestion - G Adinurani, Praptiningsih; Hendroko Setyobudi, Roy; K Wahono, Satriyo; Nindita, Anggi; Mel, Maizirwan; Sasmito, Andi; A. Nugroho, Yogo; Liwang, Tony (Elsevier, 2015)
Jatropa curcas Linn. (JcL) capsule husk was not recommended as biogas feedstocks. However for biorefinery purpose, several technologies have been conducting to solve this problem. This research reported quantity and quality comparison of Dry Husk Jcl (DH-JcL) in one phase system of batch digester compare with semi continuous digester. HDPE drum of 80 L working volume used as digester with 40 days hydraulic retention time. Feeding of DH-Jcl and solvent water was mixed on concentration of 1: 8.Research conclusion showed that semi continuous digester was better than batch digester. Biogas quality showed that methanecontent can reach 66.61 % to 83.15 % and biogas quantity in semi continuous digester can reach 0.016 m3 · kg–1 DH JcL. Theresult was not in optimize condition yet because ratio number of volatile fatty acids/ alkalinity showed 0.5, it was indicatedunstable anaerobic degradation process of DH-JcL.